Multi-filter Transit Observations of HAT-P-3b and TrES-3b with Multiple Northern Hemisphere Telescopes. (4th May 2017) - Ricci, D.; Sada, P. V.; Navarro-Meza, S.; López-Valdivia, R.; Michel, R.; Machado, L. Fox; Ramón-Fox, F. G.; Ayala-Loera, C.; Sevilla, S. Brown; Reyes-Ruiz, M.; La Camera, A.; Righi, C.; et al.
Abstract: We present a photometric follow-up of transiting exoplanets HAT-P-3b and TrES-3b, observed by using several optical and near-infrared filters, with four small-class telescopes ( D = 36–152 cm) in the Northern Hemisphere. Two of the facilities present their first scientific results. New 10 HAT-P-3b light curves and new 26 TrES-3b light curves are reduced and combined by filter to improve the quality of the photometry. Combined light curves fitting is carried out independently by using two different analysis packages, allowing the corroboration of the orbital and physical parameters in the literature. Results find no differences in the relative radius with the observing filter. In particular, we report for HAT-P-3b a first estimation of the planet-to-star radius R p / R * = 0.1112 − 0.0026 + 0.0025 in the B band which is coherent with values found in the VRIz ′ JH filters. Concerning TrES-3b, we derive a value for the orbital period of P = 1.3061862 ± 0.0000001 days which shows no linear variations over nine years of photometric observations.